A Rare Adrenal Mass in a 3-Month-Old: A Case Report and Literature Review - Ashish Garg; Elza Pollak-Christian; Navneetha Unnikrishnan (Case Reports in Pediatrics)
A three-month-old female infant presented with abdominal distention for 2 months. A large palpable mass in right upper quadrant was noted on physical exam. Abdominal ultrasound revealed a large heterogeneous mass with multiple cystic components. Mass was surgically excised and pathology was consistent with mature adrenal teratoma. Teratoma is a germ cell tumor mainly found in gonadal tissues. Occurrence of adrenal gland teratoma in children is very rare with less than 10 pediatric case reports in English literature. We present a rare case of primary adrenal tumor in an infant and a review of the literature.